A Mathematical Model of Oil and Gas Flow in the Intermittent Gas Lift Wells - (NIM: 30113002), TASMI
Intermittent gas lift is one of the artificial lift techniques used to produce oil in the mature wells with low productivity index. In the one production cycle, this technique has two processes: closed choke period and opened choke period. The closed choke period occurs when the choke is closed, but gas flows from the compressor into the gas-line. Moreover, the opened choke period begins i.e. the choke is opened to distribute gas into the annulus. When the choke is closed, the pressure in the outlet of the gas-line (choke) will increase. This is influenced by several parameters such as length of the gasline, flow rate of gas injection, pressure of gas injection, and duration of closed choke period. Meanwhile, the the pressure in the choke must be able to supply the pressure required to propel the oil from the tubing to the surface. As a result, these parameters have an important part in the oil production with intermittent gas lift and must be controlled, so that the oil production can be maximized. After the gas flow into the tubing, the gas column will form to propel the oil. This oil is a slug column that produced to the surface. Because the gas velocity is higher than the oil velocity, then the gas will penetrate the oil. As a result, the liquid film is formed on the tubing wall. In this research, the line-packing and line-drafting models are applied in gas flow on the gas-line. The model is solved using Godunov method. The solution of the model is used to calculate the pressure of the upstream choke, so that the initial value of one of the model variables in the annulus and tubing is obtained from this solution. Moreover, the model is validated with field data from literature. The result of the validation show that the model is consistent with the field data. The sensitivity analysis of several parameters is performed to determine the effect on the pressure in the choke. These parameters are length of gas-line, flow rate of gas injection, pressure of gas injection, and duration of closed choke period. Furthermore, the mathematical model of the fluid flow in the annulus and tubing is developed based on mass and momentum conservation. In the annulus and tubing, the process of the fluid flow consist of injection-elevation and production operation. The injection-elevation operation starts when the choke is opened and terminated when the top of the slug column reaches the wellhead. After that, the production operation is started. This operation is terminated when the gas column reaches to the wellhead. Moreover, a numerical simulation by the Runge-Kutta method is performed to solve the model. Furthermore, optimization model is developed to account the minimum volumes of the oil that are not produced to the surface. The modeldescribes the minimum volumes of the liquid film formed during the injection-elevation. The film volumes are influenced by several parameters: injection gas pressure, injection gas flow rate, and duration of the closed choke period. These parameter are an existing parameter in the gas-line model. As a result, the optimization model is influenced by the fluid flow dynamics model in the gas-line, annulus, and tubing. The optimization model is solved by Differential Evolution method. The optimal solutions of the injection pressure, the injection gas flow rate from the compressor, and the duration of closed choke period are obtained, as a result, the minimum volume of the liquid film can be known. Furthermore, the model can be used to design the intermittent gas lift system. Therefore, the optimization model can be used to adjust gas injection through the compressor, so that production operation errors can be minimized.